Motivasi di Balik Bubandung Ingek Pek Mulang: Kajian Karya Efendi Sanusi - Bila Fitri Pratama; Siti Nuraini Indriasih; Rahmat Prayogi; Bambang Riyadi (Jurnal IKADBUDI, 2025)
This research is entitled "The Motivational Meaning Behind Bubandung Ingek Pek Mulang: A Study of Efendi Sanusi's Work". The purpose of this research is to find out the meaning of Bubandung Ingek Pek Mulang. This research uses qualitative literature study. In Effendi Sanusi's book "Remember Where to Return", he shows how linguistic and cultural signs shape motivational meaning. The author creates a symbolic relationship between the signifier and the signified, using markers such as poetry verses that tell the story of the Big Dipper's journey to Lampung Bay and the moral message it conveys. Here, religious and moral messages are the focus. The use of these signs is intended to convey a religious message about how important it is to remember Allah at all times in life, emphasizing moral principles such as obedience, devotion, and responsibility.Penelitian ini berjudul "Makna Motivasi Di Balik Bubandung Ingek Pek Mulang: Kajian Karya Efendi Sanusi". Tujuan dari penelitian ini adalah untuk mengetahui makna dari Bubandung Ingek Pek Mulang. Penelitian ini menggunakan studi pustaka kualitatif. Dalam buku Effendi Sanusi "Ingat Tempat Kembali", dia menunjukkan bagaimana tanda-tanda linguistik dan kultural membentuk makna motivasi. Penulis menciptakan hubungan simbolis antara penanda dan petanda, menggunakan penanda seperti bait-bait puisi yang menceritakan perjalanan biduk ke Teluk Lampung dan pesan moral yang disampaikan. Di sini, pesan agama dan moral menjadi fokus. Penggunaan tanda-tanda ini dimaksudkan untuk menyampaikan pesan keagamaan tentang betapa pentingnya mengingat Allah setiap saat dalam hidup, menekankan prinsip-prinsip moral seperti kepatuhan, pengabdian, dan tanggung jawab.